Risk Factors for Severe Cutaneous Anthrax in a Retrospective Case Series and Use of a Clinical Algorithm to Identify Likely Meningitis and Evaluate Treatment Outcomes, Kyrgyz Republic, 2005–2012. (17th October 2022) - Kutmanova, Ainura; Zholdoshev, Saparbai; Roguski, Katherine M; Sholpanbay uulu, Melis; Person, Marissa K; Cook, Rachel; Bugrysheva, Julia; Nadol, Patrick; Buranchieva, Aisuluu; Imanbaeva, Lira; Dzhangazieva, Ainura; Bower, William A; et al.
Abstract: Background: US Centers for Disease Control and Prevention guidelines currently recommend triple-therapy antimicrobial treatment for anthrax meningitis. In the Kyrgyz Republic, a country with endemic anthrax, cutaneous anthrax patients are routinely hospitalized and treated successfully with only monotherapy or dual therapy. Clinical algorithms have been developed to identify patients with likely anthrax meningitis based on signs and symptoms alone. We sought to retrospectively identify likely meningitis patients in the Kyrgyz Republic using a clinical algorithm and evaluate risk factors and their outcomes by type of treatment. Methods: We conducted a retrospective chart review of cutaneous anthrax patients in the Kyrgyz Republic from 2005 through 2012. Using previous methods, we developed a highly specific algorithm to categorize patients by meningitis status. We then evaluated patient risk factors, treatments, and outcomes by disease severity and meningitis status. Results: We categorized 37 of 230 cutaneous anthrax patients as likely having meningitis. All 37 likely meningitis patients survived, receiving only mono- or dual-therapy antimicrobials. We identified underlying medical conditions, such as obesity, hypertension, and chronic obstructive pulmonary disease, and tobacco and alcohol use, as potential risk factors for severe anthrax and anthrax meningitis. Conclusions: Based on our analyses, treatment of anthrax meningitis may not require 3 antimicrobials, which could impact future anthrax treatment recommendations. In addition, chronic comorbidities may increase risk for severe anthrax and anthrax meningitis. Future research should further investigate potential risk factors for severe anthrax and their impact on laboratory-confirmed meningitis and evaluate mono- and dual-therapy antimicrobial regimens for anthrax meningitis. Abstract : Based on our analyses, treatment of anthrax meningitis may not require 3 antimicrobials, which could impact future anthrax treatment recommendations. In addition, chronic comorbidities may increase risk for severe anthrax and anthrax meningitis.